Професійна підготовка бакалаврів гуманітарних наук з міжнародних відносин в університетах Канади - Істоміна, Катерина Юріївна (Національний університет "Львівська політехніка", 2017)
У дисертації на основі проведення порівняльно-педагогічного дослідження виконано аналіз професійної підготовки бакалаврів гуманітарних наук з міжнародних відносин в університетах Канади. Відповідно до алгоритму реалізації дослідження та на основі використання системного, структурно-функціонального, андрагогічного, аксіологічного, інтеркультурного, конструктивістського, функціонального підходів обґрунтовано професійну підготовку фахівців з міжнародних відносин як сучасну педагогічну проблему, що ґрунтується на філософських, соціологічних, педагогічних, психологічних, економічних теоріях і концепціях (теорії міжнародних відносин, людського, соціального і культурного капіталу, раціонального вибору поведінки, зовнішньоекономічної діяльності, професійної діяльності, теорії кар’єрних орієнтацій, конструктивізму і когнітивізму, міжкультурної та соціальної комунікації); охарактеризовано організаційно-педагогічні засади професійної підготовки бакалаврів гуманітарних наук з міжнародних відносин в університетах Канади (узгодження провінційних і федеральних освітніх та професійних стандартів; моніторинг якості освіти; автономність університетів; принципи інтернаціоналізації, гуманізації та демократизації освітнього процесу; академічна мобільність; гнучкість змісту освітніх програм; орієнтація на академічну результативність; інтегрований характер освітніх програм; розвиток науково-дослідного потенціалу університетів; співпраця між університетами та діловим сектором, сферою промисловості, урядовими та громадськими організаціями); проаналізовано модель підготовки бакалаврів гуманітарних наук з міжнародних відносин, що охоплює цільовий, стимулювально-мотиваційний, змістовий, операційний, контрольно-регулювальний, оцінно-результативний компоненти; окреслено можливості використання передових ідей канадського досвіду у системі вищої освіти України. Уточнено зміст понять «професійна підготовка», «бакалавр гуманітарних наук», «фахівець з міжнародних відносин». Подальшого розвитку набули ідеї організації професійної підготовки майбутніх фахівців з міжнародних відносин на основі тісної співпраці університетів та потенційних роботодавців, комплексного використання традиційних та інноваційних методів навчання із застосуванням інформаційно-комунікаційних технологій, рольових ігор, навчання в громаді. В диссертации на основе проведения сравнительно-педагогического исследования выполнен анализ профессиональной подготовки бакалавров гуманитарных наук по международным отношениям в университетах Канады. В соответствии с алгоритмом реализации исследования и на основании использования системного, структурно-функционального, андрагогического, аксиологического, интеркультурного, конструктивистского подходов обоснована профессиональная подготовка специалистов по международным отношениям как современная педагогическая проблема. В ее основу положены философские, социологические, педагогические, психологические, экономические теории и концепции (теории международных отношений, человеческого, социального и культурного капитала, рационального выбора поведения, внешнеэкономической деятельности, профессиональной деятельности, теории карьерных ориентаций, конструктивизма и когнитивизма, межкультурной и социальной коммуникации). Охарактеризованы организационно-педагогические основы профессиональной подготовки бакалавров гуманитарных наук по международным отношениям в университетах Канады (согласование провинциальных и федеральных образовательных и профессиональных стандартов, мониторинг качества образования; автономность университетов; принципы интернационализации, гуманизации и демократизации образовательного процесса; академическая мобильность; гибкость содержания образовательных программ; ориентация на академическую результативность; интегрированный характер образовательных программ, развитие научно-исследовательского потенциала университетов; сотрудничество между университетами и деловым сектором, сферой промышленности, правительственными и общественными организациями). Разработана и обоснована модель подготовки бакалавров гуманитарных наук по международным отношениям, которая охватывает целевой, стимулирующий и мотивационный, содержательный, операционный, контрольно-регулирующий, оценочно-результативный компоненты. Очерчены возможности использования передовых идей канадского опыта в системе высшего образования Украины. Уточнено содержание понятий «профессиональная подготовка», «бакалавр гуманитарных наук», «специалист по международным отношениям». Дальнейшее развитие получили идеи организации профессиональной подготовки будущих специалистов по международным отношениям на основе тесного сотрудничества университетов и потенциальных работодателей, комплексного использования традиционных и инновационных методов обучения с применением информационно-коммуникационных технологий, ролевых игр, обучение в общине. The thesis represents thorough study of the contemporary system of professional training of the Bachelors of Arts in international relations at the universities of Canada conducted on the basis of comparative pedagogical research. The system of higher education in Canada prides itself on the quality of its learning environment. It has successfully established Canada among the leaders in outcomes-based pedagogy whilst its academic community continues to engage in a wide range of innovative initiatives in order to enhance students’ learning environment and stipulate academic achievements. Higher education institutions in Canada offer effective training programs within international relations as a field of study and academic major. The study presents an attempt to investigate the current state of international relations as a field of study in the context of the Canadian higher education. It has been highlighted that Canada has a long and successful tradition of professional training in international relations according to the well-developed system of higher education, respective standards and requirements. The universities of Canada are highly rated among the known education establishments, which offer programs in international relations. The positive reputation of the Canadian professional training in international relations is achieved due to well-structured classification of fields of studies, which helps to determine the optimal objectives of specific instructional programs with orientation on balanced process of studying, as well as on successful future professional activity. The thesis also contains a general overview of the respective field of study, focusing predominantly on the role and function of the given academic discipline. According to the study implementation algorithm and on the basis of systematic, structural, functional, andragogical, competence-based, person-oriented, constructivist, activity-oriented, humanistic, axiological, content-oriented, instrumental, intercultural approaches the professional training of international relations specialists as modern pedagogical issue has been justified with the help of philosophical, sociological, pedagogical, psychological, economic theories and concepts as well as theories of international relations, peoples’, social and cultural capital, rational behavioral choice, foreign economy activity, professional activity, theory of career orientation, constructivism and cognitivism, intercultural and social communication. In the course of the research, it has been clarified that international relations as a field of study gains a significant role in the context of current global trends in the development of higher education systems. The construction of transnational cooperation, analysis and solution of complex problems of today depend on professionalism of specialists in the realm of international affairs. Thus, there is the growing need for professional training of specialists in international relations. Professional training of the specialists in international relations is traditionally implemented in the system of university education. Numerous well-elaborated training programs provide students with opportunities of successful formation and development of the necessary knowledge and skills for future career. We have characterized organizational and pedagogical fundamentals of professional training of the Bachelors of Arts in international relations at the universities of Canada (harmonization of provincial and Pan-Canadian educational and professional standards, the quality of education monitoring, the autonomy of universities, the principles of internationalization, humanization and democratization of the educational process, academic mobility, flexibility of content of educational programs; focus on academic performance, integrated character of education programs, the development of research capacity of universities, cooperation of universities and the business sector, industry, government and NGOs). We have developed and justified the model of the system of professional training of the Bachelors of Arts in international relations at the universities of Canada. It includes the aim of instructional programs, motivation of students’ activity, content of instructional programs, forms and methods of instruction, learning outcomes, and assessment of students’ academic achievements. It has been discovered that the undergraduate instructional programs in international relations in Canada assist students in gaining a broad overview of multidisciplinary studies complementing each other to develop a good sense of the ways in which different disciplines approach the development of the major sphere of interest. The research contains the general overview of the main types of the instructional programs in international relations of the leading universities in Canada, namely the Bachelor of Arts, the Bachelor of Arts (with honours), the Bachelor of Arts with minor specialization. On the basis of comparative analysis, common and divergent features of Canadian and Ukrainian experience have been defined. We have outlined the possible use of advanced ideas of Canadian experience in the higher education of Ukraine. The notions «professional training», «Bachelor of Arts», «international relations specialist» are clarified. The ideas of organization of professional training of international relations specialists on the basis of closer cooperation of universities and potential employers, complex use of traditional and innovative teaching methods together with informational and communicative technologies, role plays, community-based learning have gained further development.
Профессиональная подготовка бакалавров гуманитарных наук по международным отношениям в университетах Канады
Professional training of the bachelors of arts in international relations at the universities of Canada
Keywords: бакалавр гуманітарних наук; професійна підготовка; фахівець з міжнародних відносин; професійна компетентність; професійні стандарти; бакалавр гуманитарных наук; профессиональная подготовка; специалист по международным отношениям; профессиональная компетентность; профессиональные стандарты; Bachelor of Arts; professional training; specialist in international relations; professional competence; professional standards